RESEARCH OF THE SOFTWARE OF BUDGETING`S PROCESS AND THE RECOMMENDATION FOR HIS EFFECTIVE USE IN THE INDUSTRIAL ORGANIZATION - Y. Vorontsova; A. Dobrokhodova; U. Polevikova (Вестник университета, 2016)
Research of the software of process of budgeting is presented in article, seven systems which have been divided by the principle of belonging to foreign, domestic or joint developments are allocated. Modern tools are given, their main opportunities of use in the industrial organizations are allocated. The field of the tasks solved by means of these systems is outlined. Their merits and demerits are presented. Authors of article have carried out the comparative analysis of the software of systems of budgeting by the created criteria / to the considered cuts.